A Comprehensive Model of Factors Associated With Capability to "Live Well" for Family Caregivers of People Living With Mild-to-Moderate Dementia: Findings From the IDEAL Study. (January 2019) - Clare, Linda; Wu, Yu-Tzu; Quinn, Catherine; Jones, Ian R.; Victor, Christina R.; Nelis, Sharon M.; Martyr, Anthony; Litherland, Rachael; Pickett, James A.; Hindle, John V.; Jones, Roy W.; Knapp, Martin; et al.
Abstract : Introduction: Understanding key influences on outcomes for caregivers of people with dementia is hampered by inconsistent conceptualization and measurement of outcomes and limited evidence about the relative impact of different variables. We aimed to address these issues. Methods: We analyzed data from 1283 caregivers of community-dwelling individuals with mild-to-moderate dementia in the Improving the experience of Dementia and Enhancing Active Life cohort study. We generated a "living well" latent factor from measures of quality of life, satisfaction with life, and well-being. We used structural equation modelling to derive latent variables for 7 domains reflecting caregivers' perceptions of their personal resources and experiences, and to examine the associations with caregivers' perceptions of their capability to "live well." Results: The domain of psychological characteristics and psychological health was most strongly related to living well [2.53; 95% confidence interval (CI), 2.08-2.97], followed by physical fitness and physical health (1.48; 95% CI, 1.04-1.91) and experiencing caregiving (1.34; 95% CI, 0.99-1.70). Social capitals, assets and resources (0.68; 95% CI, 0.35-1.00) and relationship with the person with dementia (−0.22; 95% CI, −0.41 to −0.03) had smaller, significant associations. Social location (0.28; 95% CI, −0.33 to 0.89) and managing everyday life with dementia (0.06; 95% CI, −0.15 to 0.28) were not significantly associated with living well. Discussion: These findings demonstrate the importance of supporting caregivers' psychological and physical health and their ability to develop and maintain positive coping strategies, as well as enabling them to maintain vital social capitals, assets and resources. Abstract : Supplemental Digital Content is available in the text.